TINJAUAN YURIDIS TENTANG KAWIN/PERNIKAHAN SECARA KONTRAK MENURUT IMPLEMENTASI PASAL 1320 DAN 1243 KITAB UNDANG-UNDANG HUKUM PERDATA (KUHPER) - Aris Setyanto Pramono; Safiulloh Safiulloh (Res Justitia : Jurnal Ilmu Hukum, 2022)
This study aims to determine whether or not a dispute over default can be resolved in a marriage or marriage that is carried out by contract. Because in the rules of the marriage law No.1 of 1974 there is no state that marriage is carried out with a certain time limit and the parties have certain purposes and clauses, and in religion as a marriage is carried out because on the basis of mutual love without any coercion and solely aims only to worship Allah Almighty / God Almighty. In one of the valid conditions in the contract or agreement in article 1320 of the Criminal Code is "lawful clause", meaning that the object promised is not an illegitimate item, not a prohibited thing either by state and religious law, so that the contract agreement whether biased is said to be valid or not and if one of the parties commits a default whether it can be said to be an unlawful act. In this study, the author used a qualitative analysis method, namely systematically compiling data obtained from interview results, field notes and other materials, so that it can be understood easily and the findings can be understood easily and informed to others. Marriage and marital problems that often occur in daily life such as infidelity, domestic violence, to the occurrence of actions that lead to criminal sanctions are something that we should not allow to continue to happen without efforts to prevent disputes, cases and conflicts of marriage or marriage. In this case, the Religious Court as the authorized body, makes efforts in resolving disputes, conflicts and marriage cases such as conducting mediation or bringing cases before the court